Formal Transformations in Islamic Building Design and their Sustainable Impact on Contemporary Architecture - Mohson, Zainab Hamid; Ismael, Zeyad Ali; Naiem, Shoula Raad; Shalal, Saba Salih (Architecture image studies scientific journal, 2025)
Form is one of the fundamental aspects associated with the evolution and change in architecture, where formal transformations can be understood as a series of processes that change the formal system to achieve new forms that suit the surrounding conditions. This is shown through the succession of appearances and evolution of forms in response to changing environmental and cultural factors. This study addresses the impact of morphological transformations on the designs of Islamic buildings, where the research problem lies in the lack of a clear understanding of how these transformations affect Islamic architecture and their future impact on modern-day architecture. The study is based on the hypothesis that the application of a set of formal transformations to the styles of Islamic buildings has contributed to the enhancement of sustainable aspects in contemporary architecture. To achieve this, the research dealt with the study of patterns of formal transformation and the comparison of architectural forms to measure their effects on sustainability. The study touched on multiple levels of transformation: total, partial, and transformation mechanisms, and reached practical application through the analysis of three architectural models: Two of the Islamic architecture of the Abbasid era (Al-Akhidar Fort and the Al-Mustansiriya School), and the third of contemporary architecture (the Louvre Museum in Abu Dhabi).